Study of maternal and prenatal outcome in pregnant women with acute hepatitis E viral infection - Mishra, Sunita; Jha, Rajesh Kumar; Thakur, Ratna; Tiwari, Sindhuja (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Hepatitis E Virus (HEV) is a major aspect of hepatitis and death in the developing countries and asymmetrical source of deaths in among of pregnant women. The objective of this study was to determine the maternal and prenatal outcome in pregnant women with acute hepatitis E viral infection in Malwa, India. Methods: Observational, cross-sectional study. The study population was pregnant women with acute hepatitis E infection confirmed by ELISA technique. Pregnant women with other hepatic viral infections were excluded. All medical and obstetric conditions and mortality were noted on the predesigned proforma. Results: Out of the total 105 admitted pregnant women with hepatitis E viral infection, 21.90% women had severe morbidity, 24.17% perinatal death and 14 (13.3%) expired before delivery. The yellowish discoloration of urine or sclera was observed in 91.42% with abdominal pain in 76.19%. Maternal mortality was higher in patients with primi (47.82%) and patients presented in second trimester (56.50%). Conclusions: The acute viral hepatitis E infection in pregnant women is associated with maternal morbidities and high mortality rate.